Deviations From Scrum Framework: Root Causes And Consequences - Mortada, Mohamad (My University, 2019)
This research is a multi-use case study that investigates companies that are using the Scrum framework. It aims to study how companies are implementing the Scrum framework and practice its agile events as daily scrum, sprint planning, sprint retrospective, and sprint demonstration. Observations and interviews have been made with different companies and developers to discover these deviations, negative and positive experiences, the causes, and its consequences on the team. These results are confirmed by an online survey that has been sent to more than 100 developers at different companies. As a result, some respondents teams are also deviating in practicing the scrum events as daily scrum, sprint planning, sprint retrospective, and sprint demonstration. At the second round interviews, scrum masters from different teams were have reported the consequences of these deviations in their teams and how they affect their teams negatively or positively.
Keywords: Agile; Scrum; practices; values; principles; negative experiences; positive experiences; deviation